PEMAKNAAN SOSOK ANIES BASWEDAN DI COVER MAJALAH TEMPO TERKAIT WACANA CALON PRESIDEN 2024 - Sidiq, Muhammad; Adrianda, Irsan (AT-TANZIR: JURNAL ILMIAH PRODI KOMUNIKASI PENYIARAN ISLAM, 2023)
The cover of magazines plays a crucial role in conveying messages and influencing public opinion, particularly through cartoon illustrations. This research focuses on Tempo magazine, known as one of Indonesia's critical media outlets, especially during the New Order regime. With the upcoming 2024 presidential election, Anies Baswedan has emerged as a presidential candidate supported by the Coalition for Change. The study titled "The Interpretation of Anies Baswedan's Figure on Tempo Magazine Covers Related to the 2024 Presidential Candidate Discourse" employs a qualitative approach using semiotic analysis to understand how caricature images on the magazine covers reflect political dynamics and public opinion. The analysis is conducted on editions of Tempo magazine published on June 25, 2022, November 6, 2022, and January 29, 2023. The primary focus is to identify signs within the illustrations using Charles Sanders Peirce's triangle of meaning, which includes icons, indexes, and symbols. The results indicate that the caricatures on the magazine covers not only represent the main news but also reflect the complex political situation, including the uncertainties surrounding Anies Baswedan's candidacy in the 2024 elections. The conclusions of this research emphasize that Tempo magazine's use of caricatures is effective in shaping opinions and capturing readers' attention, with each edition providing different meanings related to the presidential candidate discourse and political dynamics in Indonesia